Emerging therapeutic targets for osteoporosis treatment. (1st July 2014) - Chen, Minglei; Qiao, Hongzhi; Su, Zhigui; Li, Huipeng; Ping, Qineng; Zong, Li
Abstract : Introduction: To date, osteoporosis still remains a major public health burden especially for the aging populations. Over the last few decades treatments for osteoporosis have largely focused on anti-resorptive agents represented by bisphosphonates and estrogen therapy that dominated the market. Unsatisfactory efficacy, non-specificity and long-term safety of current therapies necessitate the need for new targets effectively preventing and treating of osteoporosis. Areas covered: This review expatiates on the mechanism of osteoporosis occurrence and bone remodeling cycle in detail. New targets of antiresorptive and anabolic agents based on the functions of osteoblasts and osteoclasts as well as associated signaling pathways are outlined. Expert opinion: Advanced understanding in the fields of bone remodeling, functions of osteoblasts, osteoclasts and osteocytes associated with osteoporosis occurrence offers the emerging bone-resorptive or bone-formative targets. Currently, molecules involving RANK-RANKL-OPG system and Wnt/β-catenin signaling pathway act as the most promising targets.